ESTIMASI JAMINAN PASCATAMBANG USAHA PERTAMBANGAN MINERAL BATUAN PT. X DI KABUPATEN MANOKWARI - Setiawan, Arif; Imbo, Yuldi Christiani; Paradida, Yulia Putri (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2024)
PT. X is one of the companies in Manokwari that is engaged in rock mining. Currently, the company has conducted a feasibility study and has progressed to the production operation stage. Any company that aims to upgrade its license from an Exploration Mining Business License (IUP) to a Production Operation License is required to prepare a post-mining plan document, which includes post-mining financing. The amount of this financing will be deposited in a bank as a post-mining guarantee to the government. This study aims to estimate the amount of the post-mining guarantee that will be deposited on behalf of the government. To achieve this objective, the study employs an applied research method by referring to the Minister of Energy and Mineral Resources Decree No. 1827 K/30/MEM/2018. The results of this study show that the post-mining guarantee consists of direct costs amounting to IDR 92,750,110 and indirect costs amounting to IDR 15,303,768, resulting in a total post-mining cost of IDR 108,053,878 to be deposited. Based on these findings, the post-mining guarantee will not be fully paid at once, but will be divided into three installments: in the first year, IDR 55,242,545 will be deposited, followed by IDR 33,891,302 in the second year, and IDR 23,102,571 in the third year.